Granuloma anular: un desafío diagnóstico y terapéutico Granuloma annulare: a therapeutic and diagnostic challenge - M Corigliano; RE Achenbach (Asociación Argentina de Dermatología, 2012)
Efectuamos una revisión de la etiopatogenia, clínica, histopatología, diagnósticos diferenciales y tratamiento del granuloma anular, cuyas diversas facetas constituyen un desafío para el dermatólogo clínico y en ocasiones el dermatopatólogo. A review of the ethiopathogenic, clinical features, histological patterns, differential diagnosis and therapeutics approach of the granuloma annulare are made. The different aspects of this enigmatic disease are a challenge for the clinical dermatologist and the dermopathologist.